Do State-Owned and Non-State-Owned Multinationals Behave Differently in Internationalisation? – A Case Study of Sinopec and Huawei - WEI, WEI (2012)
Internationalisation of firms has become a significant trend following the increasingly intense economic globalisation. The expansion of emerging economy multinational enterprises (EE MNEs) has reshaped the international business landscape and thus has attracted more scholars to research two fundamental types of them according to the ownership status: state-owned and non-state-owned MNEs. Utilising a theoretical framework that integrates industry-based view, resource-based view, and institution-based view, this dissertation aims to discover the distinctive internationalisation behaviours of these two types of EE MNEs compared to conventional MNEs. In specific, the dissertation examines the differences in internationalisation behaviour between state-owned and non-state-owned MNEs with regard to internationalisation speed, internationalisation path, and entry mode choices. The research uses case study approach and employs Sinopec and Huawei as case companies.